Safe and Resilient Cities in Ethiopia : CityStrength Diagnostics in Nine Regional Capitals and Dire Dawa City Administration - World Bank (World Bank, Washington, DC, 2019)
This report captures the outcomes of the TA on Strengthening Urban Resilience in Ethiopia, including City Strength Diagnostic carried out in the Dire Dawa City Administration and nine regional capitals of Ethiopia. Chapter two provides an overview of shocks and stresses in the cities, the growing hazard exposure, the impacts of climate change, and preparedness in terms of emergency response and safe building construction. It also addresses the question of what hazards cities are exposed to (now and in future), and whether they are adequately prepared. Chapter three focuses on the resilience of urban systems based on assessments in 10 sectors across the 10 cities. It answers the question whether local capacity exists to deal with shocks and stresses, and if urban systems are resilient. Each sectoral assessment is done against the five qualities of resilience to understand capacity constraints and resilience priorities. This exercise was conducted jointly by the participants in the consultations and the World Bank sectoral specialists. After determining vulnerabilities at the sectoral level, Chapter four provides a summary of the priorities at the city level that were determined during the consultation workshops. It provides details of critical actions needed to make Ethiopian cities more resilient. Designed to be accessible to a broad audience, this report presents the most relevant and actionable information that emerged from the diagnostic exercise.